UGT2B28 accelerates prostate cancer progression through stabilization of the endocytic adaptor protein HIP1 regulating AR and EGFR pathways. (28th January 2023) - Lacombe, Louis; Hovington, Hélène; Brisson, Hervé; Mehdi, Sadia; Beillevaire, Déborah; Émond, Jean-Philippe; Wagner, Antoine; Villeneuve, Lyne; Simonyan, David; Ouellet, Véronique; Barrès, Véronique; Latour, Mathieu; et al.
Abstract: The androgen inactivating UGT2B28 pathway emerges as a predictor of progression in prostate cancer (PCa). However, the clinical significance of UGT2B28 tumoral expression and its contribution to PCa progression remain unclear. Using the Canadian Prostate Cancer Biomarker Network biobank (CPCBN; n = 1512), we analyzed UGT2B28 tumor expression in relation to clinical outcomes in men with localized PCa. UGT2B28 was overexpressed in tumors compared to paired normal adjacent prostatic tissue and was associated with inferior outcomes. Functional analyses indicated that UGT2B28 promoted cell proliferation, and its expression was regulated by the androgen receptor (AR)/ARv7. Mechanistically, UGT2B28 was shown to be a protein partner of the endocytic adaptor protein huntingtin-interacting protein 1 (HIP1), increasing its stability and priming AR/epidermal growth factor receptor (EGFR) pathways, leading to ERK1/2 activation triggering cell proliferation and epithelial-to-mesenchymal transition (EMT). HIP1 knockdown in UGT2B28 positive cells, and dual pharmacological targeting of AR and EGFR pathways, abolished cell proliferative advantages conferred by UGT2B28. In conclusion, UGT2B28 is a prognosticator of progression in localized PCa, regulates both AR and EGFR oncogenic signaling pathways via HIP1, and therefore can be therapeutically targeted by using combination of existing AR/EGFR inhibitors.